Improving the efficiency of using an electric scooter in urban electromobility - Caban, Jacek; Nieoczym, Aleksander; Sokolovskij, Edgar; Drozd, Kazimierz (Transport, 2025)
The popularity of electric scooters as an individual means of transport results from their availability in the urban sharing system, ease of movement in the city and reduction of driving time compared to other means of passenger transport. The user can choose from a whole range of vehicles with different driving range and equipment with elements increasing the functionality of using the scooter. The article presents a proposal for changes to the design of a typical electric scooter. The main objective of the work is the engineering design of suspension and braking systems, in particular the swing arm suspension of the front and rear wheels and an additional disc brake. Increasing the diameter of the wheels and equipping it with a front and rear suspension system allowed for the reduction of vibrations and shocks transferred to the vehicle when driving on uneven surfaces. The results of analytical calculations confirming the positive effects of the introduced modifications were included. Adding a disc brake allowed for shortening the braking distance from 13.7 to 8.9 m, which has a positive effect on driving safety. A Finite Element Method (FEM) strength analysis was also performed, the results of which confirm the correctness of the new design. The modernized design improved the ride comfort and safety of using the electric scooter.First published online 9 February 2026